Monoenergetic 290 MeV/n carbon-ion beam biological lethal dose distribution surrounding the Bragg peak - Dylan J. Buglewicz (Nature Portfolio, 2019)
Abstract The sharp high dose Bragg peak of a carbon-ion beam helps it to deliver the highest dosage to the malignant cells while leaving the normal cells relatively unharmed. However, the precise range in which it distributes dosages that significantly induce cell death or genotoxicity surrounding its Bragg peak remains unclear. To evaluate biological effects of carbon-ion radiation through entrance to post Bragg peak in a single biological system, CHO and xrs5 cells were cultured in T-175 cell culture flasks and irradiated with 290 MeV/n monoenergetic carbon-ions with initial dosages upon entrance to the flask of 1, 2, or 3 Gy for cell survival assays or 1 Gy for cytokinesis block micronuclei assays. Under all initial dosages, the biological Bragg peak and the highest micronuclei formation was observed at the depth of 14.5 cm. Moreover, as the initial dosage increased the range displaying a significant decrease in survival fraction increased as well (P < 0.0001). Intriguingly from 1 Gy to 3 Gy, we observed a significant increase in reappearance of colony formation depth (P < 0.05), possibly indicating the nuclear fragmentation lethality potential of the carbon-ion. By means of our single system approach, we can achieve a more comprehensive understanding of biological effects surrounding of carbon-ions Bragg peak.